Methodological issues in Researching Ethnic Entrepreneurship: African Entrepreneurship in London - Nwankwo, Sonny; Madiche, Nnamdi; Ekwulugo, Frances (Senate Hall, 2004)
Ethnic entrepreneurship in Britain is frequently treated with little regard to the diversity that exists among ethnic minority groups and their approaches to entrepreneurship. This lacuna is underpinned by a lack of appreciation of the spatial and temporal contexts of entrepreneurship among many minority groups. Consequently, very little is known about how African-owned small businesses are evolving, their growth trajectories, the depth of ethnic and non ethnic-based networks that they create or are drawn into and, very importantly, how they are managing to survive. As a result, recent efforts at researching this phenomenon using normative approaches have been fuzzy and fraught with complications. Accordingly, this paper, drawing from the experience gained in carrying out a commissioned project, discusses the major difficulties in reaching and engaging African entrepreneurs in research-related endeavours and highlights the methodological approach that was applied in order to improve the process of collecting data (and the quality of data itself) from this population group.
Keywords: African entrepreneurship|ethnic businesses|research methodology|London